The Gatsby gambit [large type] - Anderson-Wheeler, Claire (Center Point Large Print, 2025)
"Freshly twenty-one and sporting a daring new bob, Greta Gatsby -- younger sister to the infamous Jay -- is finally free of her dull finishing school, and looking forward to an idyllic summer at the Gatsby Mansion, the jewel of West Egg. From its breathtaking views to its eccentric denizens, Greta is eager to inhale it all -- even to the predictable disapproval of Mrs. Dantry, Jay's exacting housekeeper. Indeed, nothing could disrupt the blissful time Greta has planned . . . except finding out that Jay's cadre of dubious friends -- Daisy and Tom Buchanan, along with Nick Carraway and Jordan Baker -- will be summering there, too. It's hard to be noticed when the luminous Daisy Buchanan is in the room, and Jordan keeps rather too-close tabs on handsome Nick Carraway for Greta's liking. But by far the worst is Daisy's boorish husband, Tom, whose explosive temper seems always balanced on a knife-edge. But soon, bad blood is the least of their problems, as a shocking event sets the Gatsby household reeling. Death has come to West Egg, and with it, a web of scandal, betrayal, and secrets. Turning sleuth isn't how Greta meant to spend her summer -- but what choice does she have, when everyone else seems intent on living in a world of make-believe?"--